2013
DOI: 10.1002/wrcr.20448
|View full text |Cite
|
Sign up to set email alerts
|

A nonparametric stochastic method for generating daily climate-adjusted streamflows

Abstract: [1] A daily stochastic streamflow generation model is presented, which successfully replicates statistics of the historical streamflow record and can produce climate-adjusted daily time series. A monthly climate model relates general circulation model (GCM)-scale climate indicators to discrete climate-streamflow states, which in turn control parameters in a daily streamflow generation model. Daily flow is generated by a two-state (increasing/ decreasing) Markov chain, with rising limb increments randomly sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…Land cover is used in hydrologic models to set parameters such as impervious cover, leaf area, and rooting depth that influence the partitioning of precipitation to evapotranspiration and runoff (De Roo et al ; Calder ; Costa et al ; Wang et al ). Hydrologic models are driven by climate data, such as precipitation and temperature, to establish the water inputs, either as rain or snow, and the potential evapotranspiration output (Easterling et al ; Teutschbein and Seibert ; Stagge and Moglen ).…”
Section: Introductionmentioning
confidence: 99%
“…Land cover is used in hydrologic models to set parameters such as impervious cover, leaf area, and rooting depth that influence the partitioning of precipitation to evapotranspiration and runoff (De Roo et al ; Calder ; Costa et al ; Wang et al ). Hydrologic models are driven by climate data, such as precipitation and temperature, to establish the water inputs, either as rain or snow, and the potential evapotranspiration output (Easterling et al ; Teutschbein and Seibert ; Stagge and Moglen ).…”
Section: Introductionmentioning
confidence: 99%
“…Water Resources Research the diurnal increments of the streamflow (Stagge & Moglen, 2013;Szilagyi et al, 2006). The shape and scale parameters of the Weibull distribution are estimated for each month from the observed diurnal increments of the streamflow.…”
Section: /2019wr025058mentioning
confidence: 99%
“…A further group of models consists of models that employ Markov chains and their variations. These models account for transition probabilities between different hydrological states (Stagge and Moglen, 2013;Bracken et al, 2014;Pender et al, 2015) and can be combined 20 with nonparametric approaches such as k-nearest neighbors (Prairie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Borgomeo et al (2015) have shown how simulated annealing can be used to generate synthetic streamflow time sequences that represent possible climate-induced changes in user-specified streamflow properties. 30 All these previously mentioned models are based on the time domain. An alternative to time-domain models is frequencydomain models (Shumway and Stoffer, 2017), which allow for the simulation of surrogate data with the same Fourier spectra as the raw data (Theiler et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation